A política de atenção aos/às idosos(as) vítimas de violência intrafamiliar de uma instituição pública de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
This paper addresses the policy attention to (the) elderly (the) victims of domestic violence a public institution of Manaus. Violence against older people is multi-causal problem today as determinants of several factors: social, economic, political and cultural rights, to demand the intervention of the Company and the Government. However, we can see is that still there are few studies that address this issue, since the first studies date back to 90 years. It is a research nature quanti held at the Department of Defense and Protection of the Elderly, a reference to violence in attention, interviews with professionals who make up the five professional staff (social workers, psychologists, lawyers and Delegate) and applied form open and closed with eight elderly victims of domestic violence, a total of thirteen participants. With the following results: the elderly are men and women whose age varies from 64 to 78 years, in relation to marital status, six elderly (as) are married, the other, an elderly widow and the other is single. As for family composition, seven elderly live with family and only one reported that elderly living alone constituting single-person household. With regard to income, six seniors are retired, elderly is a beneficiary of the BPC. And only one has no income and elderly receive help from families to meet their basic needs. Regarding risk factors, we observe the consumption of drugs and alcohol by family members who abuse their elderly. In most cases, the abuser is the child, and only an old revealed that her granddaughter was a minor. About the policy attention to the violence found that users have a positive view about the services offered by the Integrated Center, as professionals, they showed the relevance and contributions of services offered. Therefore, we analyze how it is being operationalized attention to violence in the institution of Manaus and identify the profile of the elderly victim of domestic violence served by the Center, and show that, as elderly is vulnerable to this situation, their families, too, next actions require a proactive and comprehensive and systematic monitoring both seniors and families in order to mitigate the impacts of conflicts in family dynamics and, possibly, the practices of violence against the elderly segment.
Keywords: Política de atenção à violência; Núcleo Integrado de Proteção e Defesa; Policy attention to violence; The Integrated Protection and Defense; OUTROS